The Impact of Destination Image and the Intention to Revisit: A Study Regarding Arab Tourists - Artuger, Savas; Cetinsoz, Burcin Cevdet (European Scientific Journal, ESJ, 2017)
The objective of this study is to determine the impact of destination image (cognitive and affective image) on the intention of Arab tourists to revisit Istanbul. The sample group of the study is comprised of Arab tourists who visited Istanbul in January-April 2016. Data was obtained from a total of 385 Arab tourists for the application. Descriptive analyses such as percentage, frequency as well as statistical tests such as factor analysis (confirmatory), reliability analysis were used in the analysis of the obtained data. Furthermore, Structural Equation Model (SEM) was used to analyze the impact of destination image (cognitive and affective image) on the intention of Arab tourists to revisit Istanbul. The study concluded that cognitive image did have an impact on the intention of Arab tourists to revisit Istanbul, however affective image was not effective in terms of intent to revisit.